Online Advertising Platforms and Customers Patronage of Online Retail Stores in Port Harcourt - Otuogha Iyo, Ebikoboere (Researchparks Publishing, 2025)
This study investigated the relationship between online advertising platforms and customers patronage of online retail stores in Port Harcourt. The population of the study comprised of 2,378,307 customers who patronized online retail stores in the Port Harcourt metropolis. A sample size of 400 was utilized for this study and this was derived using the Taro Yamane formula. The instrument for data collection was a structured questionnaire titled Online Advertising Platforms and Customer Patronage Questionnaire (OATCPQ). Data collected were coded into Statistical Package for Social Sciences (SPSS) version 23.0, and were analyzed using descriptive analytical statistics such as Percentages, while Pearson Product Moment Correlation (PPMC) was used for testing the hypotheses at 0.05 alpha levels. The findings of the study showed that there was significant relationship between online advertising marketing and repeat purchase in online retail stores in Port Harcourt; there was significant relationship between online advertising and referrals in online retail stores in Port Harcourt; there was significant relationship between social media marketing and brand loyalty in online retail stores in Port Harcourt; internet access has significant influence on the relationship between digital marketing and customers patronage in online retail stores in Port Harcourt, amongst others. It was concluded that digital marketing enhances repeat purchase, referrals, and loyalty to a brand; also, sales margin and revenue generation by online retail stores could sky rocket if digital marketing platforms are employed to advertise their products Based on the findings, the researcher recommended that online retail companies that are using online platforms should systemize of notifying customers of their products, as it is vital for companies to stay connected with their customers.